INSTRUMENTS AND PRODUCTS OF ISLAMIC WEALTH MANAGEMENT IN ISLAMIC FINANCIAL INSTITUTIONS - Harry Irawan; Sugianto; Marliyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Islamic Wealth Management (IWM) is an approach that integrates Sharia principles into the management of wealth for individuals and institutions. This journal discusses various instruments and products offered by Islamic financial institutions in the context of IWM. The study aims to identify and analyze products that comply with Sharia principles and evaluate the effectiveness of these instruments in meeting customer needs. The research method employed includes a literature review and secondary data analysis from Islamic financial institutions in Indonesia. The findings reveal a variety of instruments, such as Sukuk, Islamic mutual funds, and Takaful (Islamic insurance), which can be utilized for Sharia-compliant wealth management. Additionally, the journal highlights the challenges and opportunities faced by Islamic financial institutions in developing innovative and competitive IWM products. These findings are expected to contribute to the development of the Islamic finance industry and raise public awareness of the importance of wealth management aligned with Islamic principles.